Spin injection properties in trilayer graphene lateral spin valves - Liu, Y. P. (2013)
We report on the electrical injection and detection of spin accumulation in trilayer-graphene/MgO/ Permalloy lateral spin-valve (LSV) structure. Non-local spin valve signal is clearly observed in the LSV, indicating that spin coherence extends underneath all ferromagnetic contacts.We also show that low-resistivity graphene/MgO/Py junctions enable efficient spin injection and detection in LSV with high applied current density, which leads to large spin accumulation of 120 μV at room temperature. A spin diffusion length of 1.5 μm was obtained for the injector-detector separation dependence of spin valve signal measurements carried out at room temperature, while at T=10 K, the diffusion length increases to 2.3 μm.